Plasmodium sporozoite disintegration during skin passage limits malaria parasite transmission - Kehrer, Jessica; Formaglio, Pauline; Muthinja, Mendi; Weber, Sebastian; Baltissen, Danny; Lance, Christopher; Ripp, Johanna; Grech, Janessa; Meissner, Markus; Funaya, Charlotta; Amino, Rogerio; Frischknecht, Friedrich (EMBO reports, 2022)
During transmission of malaria-causing parasites from mosquitoes to mammals, Plasmodium sporozoites migrate rapidly in the skin to search for a blood vessel. The high migratory speed and narrow passages taken by the parasites suggest considerable strain on the sporozoites to maintain their shape. Here, we show that the membrane-associated protein, concavin, is important for the maintenance of the Plasmodium sporozoite shape inside salivary glands of mosquitoes and during migration in the skin. Concavin-GFP localizes at the cytoplasmic periphery and concavin(-) sporozoites progressively round up upon entry of salivary glands. Rounded concavin(-) sporozoites fail to pass through the narrow salivary ducts and are rarely ejected by mosquitoes, while normally shaped?concavin(-) sporozoites are transmitted. Strikingly, motile concavin(-) sporozoites disintegrate while migrating through the skin leading to parasite arrest or death and decreased transmission efficiency. Collectively, we suggest that concavin contributes to cell shape maintenance by riveting the plasma membrane to the subtending inner membrane complex. Interfering with cell shape maintenance pathways might hence provide a new strategy to prevent a malaria infection.